Gestão sustentável e capacidade de inovação em agroindústrias familiares do Rio Grande do Sul - Damke, Luana Inês (2017)
Sustainability and innovation are being studied and worked in several activities, sectors or spheres. In order to have success in any type of enterprise, it is necessary to know how to innovate and to be attentive to what society is demanding, and today it is known that most people want quality products and services that are innovative and do not bring damage to the environment. The main objective of this study is to identify the main management practices for sustainability and to verify their relation with the capacity for innovation in family agro-industries certified by the Family Agroindustry Program Rio Grande do Sul State. Management practices for sustainability were approached from the model of Callado (2010), initially proposed to measure business sustainability. In order to verify innovation capacity management, the Valadares scale (2012) was used, validated through a study with 243 Brazilian firms, with the aim of revealing the interrelationship between the main determinants of innovation capacity. The study was carried out in two methodologically distinct phases. The first phase of the study was characterized as qualitative and was conducted from exploratory interviews with three family agroindustries of the Rio Grande do Sul State and the director of the Department of Family Agribusiness, Marketing and Supply. The results of this phase allowed concluding that, in the analyzed companies, the use of the Sabor Gaúcho seal has no significant influence on sustainable management practices and the management of innovation capacity. However, there is a direct relationship between management practices for sustainability and management of innovation capacity. The more sustainable the organization is, the greater will be its ability to innovate. The second stage of the study was characterized as quantitative and comprised the realization of a search survey with one hundred and twenty eight RS family agro-industries, in order to analyze the existence of management practices for sustainability and its relation with the management of innovation capacity. In general, it has been found that there are sustainable management practices and there are positive associations between some factors related to the management of innovation capacity. In addition, we sought to compare the adoption of innovation capacity management with the management of sustainable practices through the Mann-Whitney test, whereby it was found that in most cases when family agro-industries have a high degree of sustainable practices they will also have a high degree of innovation capacity.